2017
DOI: 10.1016/j.jsams.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lower-body compression garments on walking performance and perceived exertion in adults with CVD risk factors

Abstract: 7Objectives. Compression garments (CG) are used by athletes in attempts to enhance performance 8 and recovery, although evidence to support their use is equivocal. Reducing the exertion 9 experienced during exercise may encourage sedentary individuals to increase physical activity. The 10 aim of this study was to assess the effect of CG on walking performance (self-paced and enforced 11 pace) and rate of perceived exertion (RPE) in adults who presented with two or more CVD risk 12 factors. Participants (n=15, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The meta-analyses of our umbrella review indicate a trivial effect of wearable smart garments on rate of perceived exertion in line with previous studies in athletes [ 25 ] and non-athletes [ 26 ]. In addition, we observed that wearing smart garments with optimized compression, fitting, and skin contact characteristics has a small effect on proprioception.…”
Section: Discussionsupporting
confidence: 85%
“…The meta-analyses of our umbrella review indicate a trivial effect of wearable smart garments on rate of perceived exertion in line with previous studies in athletes [ 25 ] and non-athletes [ 26 ]. In addition, we observed that wearing smart garments with optimized compression, fitting, and skin contact characteristics has a small effect on proprioception.…”
Section: Discussionsupporting
confidence: 85%
“…The mid-back region was specifically chosen as it was shown to be associated with a lower energy cost than most other forms of load carriage [33,34]. Following 4-min of quiet standing, the subjects began walking at 2.7 km/h at 0% incline, stage 2 is at 2.7 km/h at 5% incline, and then stage 3 was the start (Stage 1) of the Bruce protocol consisting of further increases in grade and speed continue, at 3-min intervals, until the subject reaches volitional exhaustion (Run-7410, Italy) (S1 Table) [35]. During the GXTs, HR (Polar-T3, Kempele, Finland), oxygen uptake, _ VE (L�min -1 ) throughout the tests were recorded using Breath-by-Breath technology (Metalyzer II-R2, CORTEX, Germany) and the data collected and exercise duration were automatically recorded by the software.…”
Section: Graded Exercise Testsmentioning
confidence: 99%